Bakery Bread Production System Analysis with Failure Mode and Effect Analysis Method: Case Study of the Armina Food Bread Business - Pradana, Fauzi Yoga; Indiyanto, Rus (Journal La Multiapp, 2024)
Bread was first developed during the Mesopotamian culture in the Egyptian region 10,000-12,000 years ago. Bread is a food product processed from fermenting wheat flour with yeast or other rising agents, then baking. The development of bread in Egypt then spread to Greece until it finally spread throughout Europe. Armina Food Bread Business in Gresik is a business that operates in the field of bread production. However, Armina Food's bread business experienced problems in bread production which was not optimal and stable, especially in terms of bread sales which experienced a decline due to bread production defects. Research regarding the risks of bread production was carried out at Armina Food Bakery Business using the Failure Mode and Effects Analysis (FMEA) method. FMEA is an analysis technique that identifies production process failures and plans to prevent them from happening again. Bread production risk analysis is carried out by identifying and measuring the risks of fresh bread production. The FMEA method aims to identify risks by considering the criteria of Severity (S), Occurrence (O), and Determination (D). The research results show that the highest risk lies in raw materials (differences in the quality of raw materials from each supplier), production costs (damage to machinery and equipment), and products (competition with other products). Based on risk analysis of bread production using the FMEA method, it was found that the highest risks lie in raw materials, production costs and product.